Minimum BER transmit beamforming for MIMO-OFDM systems with finite rate feedback - Liang, Yang-Wen; Schober, Robert; Gerstacker, Wolfgang (IEEE International Conference on Communications, 2008)
In this paper, we consider minimum bit error rate (BER) beamforming (BF) for multiple-input multiple-output orthogonal frequency division multiplexing (MIMO-OFDM) systems. In particular, assuming perfect channel state information (CSI) at the transmitter we optimize cyclic BF filters (C-BFFs) for minimization of the average BER and the maximum sub-carrier BER, respectively. If the C-BFF length Lg is equal to the number of sub-carriers Nc, closed-form solutions to both optimization problems exist. For the practically relevant case L g < Nc we present numerical methods for calculation of the optimum C-BFFs. For finite-rate feedback channels we provide a global vector quantization (GVQ) scheme for codebook design. Simulation results for typical IEEE 802.11n channels confirm the excellent performance of the proposed minimum BER BF schemes for both uncoded and coded MIMO-OFDM systems. ©2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03